Nano LiMn2O4 with spherical morphology synthesized by a molten salt method as cathodes for lithium ion batteries - Zhao, Xuan (2013)
The compound, LiMn2O4 is synthesized by a one-pot molten salt method using NaCl–KCl (1 : 1) as the eutectic melt at various temperatures (T) from 700 to 850 °C and characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Rietveld refinement, surface area and density methods. SEM showed that all the spinel phases LiMn2O4 consist of 1–5 μm sized spherical particles, each of which is composed of [similar]50 nm nano-sized aggregates. TEM images show spherical particles with hollow type morphology when the synthesis T is above 800 °C. The cubic lattice parameter, 8.235 (±0.002) Å did not vary much with the T in the range 700–850 °C, which is proven by the similar Mn3+ and Mn4+ amount through XPS results, whereas the surface area varied from 15.6 to 10.3 m2 g−1. The cyclic voltammograms showed the characteristic two-step redox peaks at 3.9/4.1 and 4.1/4.2 V vs. Li for all the compounds in agreement with literature reports. Galvanostatic cycling studies were carried out in the range, 3.5 to 4.3 V vs. Li showed that the LiMn2O4 prepared at 800 °C has the highest discharge capacity of 124 mAh g−1 at second cycle at 0.25 C-rate, and it showed a capacity retention of 96% at 1 C, 2 C and 5 C-rates at the end of 50 cycles. Long-term cycling at 2 C-rate, up to 700 cycles showed a capacity retention of 81%. Thus, LiMn2O4 obtained at 800 °C with uniform hollow spherical particles shows the best electrochemical properties. Complementary electrochemical impedance spectroscopy (EIS) and galvanostatic intermittent titration technique (GITT) studies were carried out and the apparent Li-ion diffusion coefficients (DLi+) were calculated as a function of the applied voltage. The DLi+ values from GITT range from [similar]0.1 to 5 × 10−10 cm2 s−1. The values decrease with an increase in the applied voltage and show two minima in good agreement with the available literature data.